Pyrolysis of polyethylene terephthalate over carbon-supported pd catalyst - Park, Chanyeong; Kim, Soosan; Kwon, Yeonghwan; Jeong, Chaehyeon; Cho, Yujin; Lee, Chang Gu; Jung, Seungho; Choi, Kwon Young; Lee, Jechan (Catalysts, 2020)
Pyrolysis of polyethylene terephthalate (PET) produces polycyclic hydrocarbons and biphenyl derivatives that are harmful to human health and the environment. Therefore, a palladium metal catalyst (5 wt.% Pd loaded on activated carbon) was used to prevent the formation of harmful materials. When a Pd catalyst/PET ratio of 0.01 was applied in pyrolysis of PET, it did not show a meaningful difference in the generation of polycyclic hydrocarbons and biphenyl derivatives. However, when a Pd catalyst/PET ratio of 0.05 was used during pyrolysis, it prevented their formation and generation at experimental temperature ranges (400–700◦C). For example, the concentration of 2-naphthalenecarboxylic acid produced, which is a typical polycyclic hydrocarbon material, was reduced by 44%. In addition, the concentration of biphenyl-4-carboxylic acid, which is contained in biphenyl derivatives, was reduced by 79% compared to non-catalytic pyrolysis at 800◦C. This was because the ring-opening reaction and free radical mechanism caused by the Pd catalyst and thermal cracking were dominant during the pyrolysis of PET. Apart from these materials, amine compounds were generated as products of the pyrolysis of PET. Amine concentration showed a similar trend with polycyclic hydrocarbons and benzene derivatives. Based on these results, the total concentration of polycyclic hydrocarbons and biphenyl derivatives was compared; the results confirmed that the concentrations of all substances were reduced. This research suggests that a metal-supported catalyst will help create a more environmentally friendly and reliable method of industrial plastic waste disposal.
Keywords: Pd catalyst; Pollution control; Polyethylene terephthalate (PET); Pyrolysis; Waste disposal